Possible association between heavy computer users and glaucomatous visual field abnormalities: a cross sectional study in Japanese workers. Issue 12 (16th November 2004) - Tatemichi, Masayuki; Nakano, Tadashi; Tanaka, Katsutoshi; Hayashi, Takeshi; Nawa, Takeshi; Miyamoto, Toshiaki; Hiro, Hisanori; Sugita, Minoru
Abstract : Study objective: To study the association between computer use and visual field abnormalities (VFA) and to assess whether heavy computer users have an increased risk of glaucoma. Design: Cross sectional multicentre study. Subjects and observation procedures: A total of 10 202 randomly selected Japanese workers (mean (SD) age 43.2 (9.8) years) were screened for VFA using the frequency doubling technology perimetry (FDT-VFA), in addition to undergoing a general medical check up, and then ophthalmologically examined. Information about their computer use and refractive errors was obtained from a questionnaire and interview, respectively. Main results: As a result of FDT test, 522 and 8602 subjects were positive and negative for FDT-VFA, respectively. A significant (p = 0.004) interaction was found between computer use and refractive errors regarding the risk of FDT-VFA. In stratified analysis, heavy computer users with refractive errors showed a significant positive association with FDT-VFA (odds ratio (OR) = 1.74, 95% confidence interval (CI) 1.28 to 2.37), while those without refractive errors did not. Comparison of 165 subjects with an ophthalmological diagnosis of glaucoma and 2918 controls showed that the OR for glaucoma of heavy computer users with refractive errors was 1.82 (95% CI 1.06 to 3.12). Of 165 subjects with glaucoma, 141 had refractive errors, especially myopia (96.4%, 136 of 141). Conclusions: Although there are limitations to this study, such as its cross sectional design, heavy computer users with refractive errors seem to have an increased risk of FDT-VFA. Glaucoma might be involved in an underlying disease and myopia in a risk factor for FDT-VFA.